Student Motivation Increases: The Impact of the Free Nutritional Meal Program on Attendance (MBG) - Arina, Ida; Sutini, Ai; Anggraeni Dewi, Dinie; Mulyati, Tita (IJORER : International Journal of Recent Educational Research, 2026)
Objective: : Quality education is a fundamental right of every child, however many students, particularly those in resource-limited areas, face challenges in accessing education. This study aimed to explore the impact of a free nutritious meal program on student attendance and motivation in three sub-districts. Using a mixed-methods approach, quantitative data were collected through surveys involving 52 students and 34 teachers, while qualitative data were obtained through in-depth interviews. The results showed that average student attendance increased from 80% to 95% after program implementation, which aligns with teachers' reports of increased student enthusiasm for learning. These findings indicate that adequate nutrition contributes to increased student motivation and engagement. While this study provides valuable insights into the program's effectiveness, its focus on three sub-districts limits the generalizability of the results. Therefore, future research is recommended to involve a wider area and employ a longitudinal approach to assess the program's long-term effects. These findings have important implications for education policy, highlighting the need for continued support for the nutritious meal program to improve access to and quality of education.